2001
DOI: 10.1021/la001170s
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nanostructures by Hydroxylamine Seeding of Gold Nanoparticle Templates

Abstract: Hydroxylamine-seeding of colloidal gold particles has been used to fabricate gold nanostructures on a SiO2 substrate. Gold nanoparticles (15 nm diameter) were randomly deposited on a SiO2 surface that had been modified with aminopropyltrimethoxysilane (APTS). The nanoparticles were then manipulated using a scanning force microscope (SFM) tip to produce 1-D templates for gold deposition. We demonstrate the utility of this approach by fabricating a gold nanowire by using 13 nanoparticles as a template. The junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 30 publications
2
71
0
1
Order By: Relevance
“…Although the small size of 1.4 nm Nanogold makes it ideal for preserving the proper binding and function of a labeled ligand, these clusters were not large enough to be located directly in EM projection images and in most tomograms derived from stained cell sections. We therefore adapted autometallography and nanoparticle seeding techniques that are used to enlarge 1.4 nm Nanogold clusters by selectively depositing silver and/or gold atoms onto their surfaces (Busbee et al, 2003;Daniel and Astruc, 2004;Gole and Murphy, 2004;Hainfeld and Furuya, 1995;Hainfeld et al, 1999;Jana et al, 2001;Meltzer et al, 2001;Okitsu et al, 2005;Zou et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the small size of 1.4 nm Nanogold makes it ideal for preserving the proper binding and function of a labeled ligand, these clusters were not large enough to be located directly in EM projection images and in most tomograms derived from stained cell sections. We therefore adapted autometallography and nanoparticle seeding techniques that are used to enlarge 1.4 nm Nanogold clusters by selectively depositing silver and/or gold atoms onto their surfaces (Busbee et al, 2003;Daniel and Astruc, 2004;Gole and Murphy, 2004;Hainfeld and Furuya, 1995;Hainfeld et al, 1999;Jana et al, 2001;Meltzer et al, 2001;Okitsu et al, 2005;Zou et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The FSF procedure described above was modified to include a preembedding gold-enlarging technique for HPF cells by adapting approaches that involve silver or gold enhancement at room temperature (Danscher, 1981;Hacker et al, 1988;Hainfeld and Furuya, 1995;Scopsi, 1989), gold-toning (Sawada and Esaki, 2000), seed-mediated gold-enlarging (Busbee et al, 2003;Daniel and Astruc, 2004;Gole and Murphy, 2004;Handley, 1989;Jana et al, 2001;Meltzer et al, 2001;Okitsu et al, 2005;Zou et al, 2006) and a FSF-based silver-enhancement procedure (Morphew et al, 2007). To avoid the background that results from spontaneous autonucleation, we designed a three-step enlarging protocol in which silver enhancement was used to slightly enlarge the Nanogold, the silver shell was coated by gold toning to make it insoluble in osmium, and the particles were further enlarged to 10 -16 nm using gold enhancement.…”
Section: Silver Enhancement/gold-toning/gold Enhancement During Fsf Omentioning
confidence: 99%
“…Electrical control typically requires wire connections. Approaches to building nanowaveguides [37] and nanowires [40], discussed later in this paper, may help here.…”
Section: Actuators 1) Artificial Molecular Machinesmentioning
confidence: 99%
“…For example, we have shown that a pattern of gold nanoparticles can be used as a template for the electroless deposition of additional gold. Gold wires of arbitrary geometry can be built by first manipulating the particles into the desired geometry and then linking them by immersion of the sample in the electroless solution with a specific set of parameters such as immersion time, concentration, and so on [40].…”
Section: E Linking and Embeddingmentioning
confidence: 99%
“…1,2 Green nanoscience/nanotechnology is the use of green chemistry principles to design nanoscale products, enhance nano-material production and importantly, to evaluate the toxicity of nanomaterials. 3 Green chemistry should be integrated into nanotechnologies at the source especially when nano-materials are to be used in medical applications, which include imaging, drug delivery, disinfection and tissue repair.…”
Section: Introductionmentioning
confidence: 99%